Competitive adsorption of phosphate with sulfate, humic acid, and fulvic acid by allophane in different parent materials in Central Java - Lilia Fauziah; Eko Hanudin; Sri Nuryani Hidayah Utami (Jurnal Ilmu Pertanian, 2022)
Andisol is a soil that has andic properties and develops from volcanic parent materials, especially ash. Andic soil properties are formed due to weathering of tephra or other parent materials that contain volcanic glass in large quantities. The main components of soil-forming Andisol are amorphous (short-range-order) minerals, such as allophane, imogolite, ferrihydrite, and Al/Fe-humus complexes. The existence of short-range-order minerals causes Andisol to have high P-tapping ability, but efforts to lower the amount of P plunged with organic and inorganic an-ons have not been widely studied. This study aimed to compare the ability of humic acid, fulvic acid, and sulfate in suppressing P adsorption by amorphous minerals from the Andisol of Mount Dieng, Merbabu, and Sumbing. The highest calculation of % ferrihydrite was found at the location of Mount Merbabu with a value of 3.05%, while the % allophane + imogolite was determined by the content of Sio in the ground. The calculation results showed that the highest was found at the location of Mount Sumbing with a value of 7.17%. Based on TEM analysis, Mount Sumbing has allophane diameter of 2.24 – 5.93 nm and the imogolite length of 24 – 187 nm.